The Socio-linguistic Profiles, Identities, and Educational Needs of Greek Heritage Language Speakers in Chicago - Zoe Gavriilidou; Lydia Mitits (National Research University Higher School of Economics, 2021)
The present study aims to further the research on heritage language speakers (HLSs) by providing the socio-linguistic profiles and identities of an uninvestigated community of heritage speakers, namely the Greeks of Chicago, thus offering data for a less-studied HL, Greek. The participants were fifty-four (N=54) first, second, and third-generation Greek HLSs. The socio-linguistic data were collected through an online survey, while identification with Greek culture as well as ethnic attachment and practice of Greek traditions were investigated through the content analysis of data from the Greek Heritage Language Corpus. The results of the study are discussed with respect to how they can improve our knowledge of the educational needs of Greek HL learners. This research-based knowledge can be employed for addressing the academic needs of HL learners through educational programs. The authors propose an agenda for a more linguistically and culturally responsive education program for HL learners, in general, and Greek HL learners in diasporic communities, in particular.